The Collaborative Innovation and Improvement Network (COIIN): Effect on donor yield, waitlist mortality, transplant rates, and offer acceptance. Issue 4 (14th November 2019) - Wey, Andrew; Foutz, Julia; Gustafson, Sally K.; Carrico, Robert J.; Sisaithong, Kristen; Tosoc‐Haskell, Henrisa; McBride, Maureen; Klassen, David; Salkowski, Nicholas; Kasiske, Bertram L.; Israni, Ajay K.; Snyder, Jon J.
Abstract : The Organ Procurement and Transplantation Network implemented the Collaborative Improvement and Innovation Network (COIIN) to improve the use of donors with kidney donor profile index >50%. COIIN recruited 2 separate cohorts of kidney transplant programs. Cohort A included 19 programs of 44 applicants (January 1, 2017, to September 30, 2017), and cohort B included 39 programs of 47 applicants (October 1, 2017, to June 30, 2018). We investigated the effect of COIIN on kidney yield (number of kidneys transplanted from donors from whom any organ was recovered), offer acceptance, deceased donor transplant rates, and waitlist mortality rates for January 1, 2016, to March 31, 2019. COIIN did not notably affect kidney yield or waitlist mortality rates. Cohort A, but not cohort B, had significantly higher deceased donor transplant and offer acceptance rates during its intervention period than programs not in COIIN (adjusted transplant rate ratio: cohort A, 1.08 1.171.27, cohort B, 0.94 1.011.08 ; adjusted offer acceptance ratio: cohort A, 1.08 1.181.29, cohort B, 0.93 1.001.08 ). Thus, COIIN improved the use of kidneys at programs in cohort A but not at those in cohort B. Further research is necessary to understand the different effects for cohorts A and B, and further monitoring of posttransplant outcomes is required. Abstract : The authors find higher transplant and offer acceptance rates for a subset of programs in the Collaborative Improvement and Innovation Network and determine that further research is necessary to understand the different effects across programs.